2021
DOI: 10.3390/jcm10030446
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Organ Involvement in COVID-19: Beyond Pulmonary Manifestations

Abstract: Coronavirus Disease 19 (COVID-19), due to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has become an on-going global health emergency affecting over 94 million cases with more than 2 million deaths globally. Primarily identified as atypical pneumonia, it has developed into severe acute respiratory distress syndrome (ARDS), a multi-organ dysfunction with associated fatality. Ever since its emergence, COVID-19 with its plethora of clinical presentations has signalled its dynamic nature and versat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 122 publications
0
103
0
6
Order By: Relevance
“…The evidence of excessive inflammatory activity in severe COVID-19, captured during the early phases of the pandemic, prompted the investigation of the clinical role of specific biomarkers of inflammatory and immunomodulating pathways, particularly C-reactive protein (CRP), white blood cell count (WBC), neutrophils, lymphocytes, platelets, procalcitonin, ferritin, and serum amyloid A [ [3] , [4] , [5] , [6] ]. Additional research has shown that patients with COVID-19 can also experience structural and functional abnormalities of specific organs and systems, e.g., cardiovascular, hematological, gastrointestinal, and neurological, in addition to the well-known respiratory compromise, characterized by the development of interstitial pneumonia and acute respiratory distress syndrome (ARDS) [ [7] , [8] , [9] ]. In particular, COVID-19 patients might present with subclinical or overt evidence of myocardial necrosis, which might manifest as acute coronary syndrome, myocarditis, arrhythmias, or heart failure [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence of excessive inflammatory activity in severe COVID-19, captured during the early phases of the pandemic, prompted the investigation of the clinical role of specific biomarkers of inflammatory and immunomodulating pathways, particularly C-reactive protein (CRP), white blood cell count (WBC), neutrophils, lymphocytes, platelets, procalcitonin, ferritin, and serum amyloid A [ [3] , [4] , [5] , [6] ]. Additional research has shown that patients with COVID-19 can also experience structural and functional abnormalities of specific organs and systems, e.g., cardiovascular, hematological, gastrointestinal, and neurological, in addition to the well-known respiratory compromise, characterized by the development of interstitial pneumonia and acute respiratory distress syndrome (ARDS) [ [7] , [8] , [9] ]. In particular, COVID-19 patients might present with subclinical or overt evidence of myocardial necrosis, which might manifest as acute coronary syndrome, myocarditis, arrhythmias, or heart failure [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Ever since its outbreak in December 2019, in Wuhan, China, SARS-CoV-2 has rapidly spread throughout the country, reaching the first epicenter in the city of Hubei and, shortly thereafter, the globe. 3 6 The clinical outcomes observed in patients infected with SARS-CoV-2 are variable, ranging from asymptomatic cases to acute respiratory discomfort and multiorgan failure. 7 Among the most common COVID-19 symptoms are cough, fatigue, headache, loss of taste and smell, myalgia and sputum, and diarrhea (mild outcome); and cyanosis, dyspnea, thoracic pain, shortness of breath, hypoxemia, severe pneumonia, pulmonary edema, and multiple organ failure (severe outcome).…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 10 In addition to the commitment of lungs, other systems may be severely affected, in particular, digestive, cardiovascular, epithelial, renal, and central nervous system. 6 Nevertheless, pulmonary tissue involvement is of greatest concern since it is the one involved in the development of acute respiratory distress syndrome (ARDS) and the risk of death. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…skin lesions, neurological, renal and cardiac dysfunction) 19,20 . In our cohort of patients, skin lesions were seen as COVID-19-associated papulovesicular exanthema scattered in trunk and mild pruritus (Fig.…”
Section: Resultsmentioning
confidence: 99%